Pengaruh Kompetensi, Budaya Organisasi, dan Disiplin terhadap Kinerja Pegawai pada Perpustakaan Universitas Sumatera Utara - Doni Kristopel Sinaga; Anton A.P. Sinaga; Elperida J. Sinurat (MAMEN: Jurnal Manajemen, 2026)
This study examines the influence of competence, organizational culture, and discipline on employee performance at the Library of the University of Sumatera Utara. The research is grounded in the crucial role of libraries in supporting the Tri Dharma of Higher Education and the need for optimal employee performance to ensure effective library services and operations. Using a correlational and associative approach, data were collected through a survey using questionnaires distributed to all 71 library employees, applying a saturated sampling method. The data were analyzed using multiple linear regression to assess both partial and simultaneous effects of the independent variables on employee performance. The findings reveal that competence, organizational culture, and discipline have a positive and significant impact on employee performance. The coefficient of determination (R²) is 0.528, indicating that 52.8% of employee performance can be explained by these three variables, while the remaining 47.2% is influenced by other factors not examined in this study. The study recommends enhancing employee competence through continuous development programs, providing motivation to encourage skill improvement, fostering an adaptive organizational culture, and ensuring consistent discipline management. These efforts are essential to improving employee performance and strengthening the overall effectiveness of the institution.